Sensitivity to energy technology costs: A multi-model comparison analysis. (May 2015) - Bosetti, Valentina; Marangoni, Giacomo; Borgonovo, Emanuele; Diaz Anadon, Laura; Barron, Robert; McJeon, Haewon C.; Politis, Savvas; Friley, Paul
Abstract: In the present paper we use the output of multiple expert elicitation surveys on the future cost of key low-carbon technologies and use it as input of three Integrated Assessment models, GCAM, MARKAL_US and WITCH. By means of a large set of simulations we aim to assess the implications of these subjective distributions of technological costs over key model outputs. We are able to detect what sources of technology uncertainty are more influential, how this differs across models, and whether and how results are affected by the time horizon, the metric considered or the stringency of the climate policy. In unconstrained emission scenarios, within the range of future technology performances considered in the present analysis, the cost of nuclear energy is shown to dominate all others in affecting future emissions. Climate-constrained scenarios, stress the relevance, in addition to that of nuclear energy, of biofuels, as they represent the main source of decarbonization of the transportation sector and bioenergy, since the latter can be coupled with Carbon Capture and Storage (CCS) to produce negative emissions. Highlights: Results of sensitivity analysis of energy technologies for three energy-economic models. In-depth analysis of sign of change and key-uncertainty drivers in a multi-model context. Report on robust findings on what uncertainty sources are key in shaping future emissions. Use of alternative metrics for sensitivity analysis. First integrated assessment model comparison to look at extensive sensitivity analysis of technology cost.